Controversies in applying the Abortion Act to Down syndrome. (June 2019) - Habiba, Marwan
Recently published data from the UK pointed out that the number of abortions performed under Ground E of the Abortion Act 1967, which allows abortion for foetal abnormalities, was far lower compared to the number of pregnancy terminations where foetuses had Down syndrome. This prompted calls for the matter to be rectified. This article explores the issues raised and argues that rather than being a concern; the discrepancy is consistent with moral uncertainty or a non-judgmental approach. This is, perhaps fortuitously, in tune with recognized conceptualizations of functioning ability. Debate about what constitutes substantial risk may be resolved in those conditions where a diagnosis can be confirmed. But clinical presentations of those affected can vary and there is no necessary link between functional abilities and suffering. Despite the ambiguities, some practitioners have resolved in favour of late abortion in pregnancies with Down syndrome. It is tempting to develop inferences from these cases, but advancing a convincing argument that may encompass all affected cases requires agreement on underpinning assumptions. Given the polarized debate in this area, it is perhaps best to acknowledge the reality of diverse ethical viewpoints.